Urban tree management: For the sustainable development of green cities. - (:unkn) unknown (Wiley-Blackwell, 2016)
Urban tree management is the key basis for greener cities of the future. It is a practical discipline which includes tree selection, planting, care and protection and the overall management of trees as a collective resource. Urban Tree Management aims to raise awareness for the positive impacts and benefits of city trees and for their importance to city dwellers. It describes their advantages and details their effects on quality of urban life and well-being aspects that are increasingly important in these times of progressing urbanisation.
Keywords: Umweltschutz; Klima; Stadtklima; Stadtökologie; Baum; Baumpflanzung; Baumschutz; Grünfläche; Lehrbuch; Stadtgrün; Begrünung; Nachhaltigkeit; Klimawandel; Klimaanpassung; Stadtbaum; Dendrologie; Baumpflege